A didática e a prática escolar: abordagens e objeto - FARIAS, Jhulio Paes (2019)
There is still a great association of didactics to technicalism, which aims to assimilate the ideas of education. The discipline is superficial, difficult to understand, subordinate to a know-how of easy manipulation, it is not critical, unable to associate the subject with a practical practice, which is easy to deal with thoughts and attitudes. Make a contribution to work as a way to contribute to the development of this area of education that is important for school education. The objective of this work is to emphasize didactics as a facilitator of education, which has the power to cross as several barriers found in the social, educational and cultural context. This work was based on authors such as Paulo Freire (2018), Ilma Passos de Alencastro Veiga (2011) and (2012), Vera Maria Candau (2009) and (2014), José Carlos Libâneo (2013)) and (2014) ) among others. Among the results of the research, I inform you that it is a first section if you understand that the didactics has changed over time and the number of times that mr. In the second section, it can be seen that Didactics, that is, is not enough to promote teaching or learning, but if it is correct, when it comes to pedagogical processes, are guaranteeing the quality of teaching and learning. Therefore, the didactics must be included in the purposes of teaching, giving support to the instruments and activities. He concluded that, no matter how technicist the didactic seems essential for educational planning, the application of activities and teachings.